Вплив четвертої промислової революції на ринок праці і систему підготовки кадрів - Ілляшенко, Сергій Миколайович; Ілляшенко, Наталія Сергіївна (My University, 2022)
Сформовано інформаційно-аналітичне підґрунтя удосконалення системи інфраструктурного забезпечення (її підсистеми кадрового забезпечення) інноваційного розвитку України в умовах четвертої промислової революції.

The information and analytical basis for improving the system of infrastructure support (its personnel support subsystem) of innovative development of Ukraine in the conditions of the fourth industrial revolution has been formed.
The impact of the fourth industrial revolution on the labor market and the training system
Keywords: кадрова політика; ринок праці; четверта промислова революція; personnel policy; labor market; Fourth Industrial Revolution